Good Governance of Local Authorities and Its Role in Promoting Sustainable Development Goals - Brahim Meziani (Pegem Journal of Education and Instruction, 2026)
This research paper aims to examine the topic of good governance of local authorities and its role inpromoting sustainable development goals, through analyzing the fundamental concepts related to governance and local authorities, and clarifying the relationship between them